Promoting the forgiveness in fremarital counseling as a way to get a successful marriage - Arafani, Adnan (COUNS-EDU: The International Journal of Counseling and Education, 2017)
Forgiveness is capable to create a change in cognitions, emotions, and behaviors toward somebody who committed a hurtful act, it can be a useful tool for counselor to deal with client’s problems including marital issues. One of the major issues in marriage is divorce. Meanwhile, the previous studies proved those individuals who experienced premarital counseling gained a high level of marital satisfaction. This article literately reviews how forgiveness can be used as a main topic in premarital counseling as an effort to achieve a successful marriage